Hypoxia: A key feature of COVID-19 launching activation of HIF-1 and cytokine storm - Mozhgan Jahani; Sadat Dokaneheifard; Kamran Mansouri (BMC, 2020)
Abstract COVID-19, disease caused by the new coronavirus, SARS-CoV-2, appeared in the end of 2019 and was rapidly spread in most countries. This respiratory virus has different symptoms from moderate to severe, and results in lung pneumonia following acute respiratory distress syndrome (ARDS) and patient's death in severe cases. ARDS is a severe form of acute lung injury that is caused by high inflammatory response of the innate immunity cells. Hypoxia is the common feature in the inflammatory sites with having various impacts on this condition by induction of some factors such as hypoxia inducible factor-1α (HIF-1α). HIF-1α regulates some important cellular processes including cell proliferation, metabolism and angiogenesis. Furthermore, this factor is activated during the immune responses and plays important roles in the inflammation site by inducing pro-inflammatory cytokines production through immune cells. So, in this study the possible effect of the HIF-1α on the COVID-19 pathogenesis with emphasizes on its role on innate immunity response has been discussed.